Love, intimacy and online dating - Portolan, Lisa, author.
1 online resource (107 pages)
Keywords: "Love, Intimacy and Online Dating: How a Global Pandemic Redefined Romantic Relationships is an innovative work that explores the concept of intimacy during the COVID-19 pandemic. The book provides an overview of the online dating world and apps, the use of which gradually became common as the pandemic restricted people's interaction in the physical world. The author's extensive research conducted during the pandemic posits a comprehensive understanding of the individual's motivation to join a dating app and explores its varied aspects"--